Pengembangan Paket Pembelajaran Kerajinan Tangan dan Kesenian (KTK) di Kelas III Sekolah Dasar - Amir Amir (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Developing Instructional Package of Handicraft and Arts Subject for the Third Grade of Elementary School. Instructional process of handicrafts and arts subject in elementary schools have not yet optimally developed. One of the causes is that the textbooks used have not so far been organized based on prescriptive learning theories, and that teachers' guide is not available. This study was designed to develop an instructional package based on prescriptive learning theories, which is equipped with such components as manual, specific learning objectives, description of learning contents, summaries, exercises, answer key, and feedback. It can be said that this instructional package meets the requirements for being disseminated.